(untitled) (Bangladesh Journal of Zoology, 2020)
Water pollution poses a threat of heavy metal accumulation in aquatic animals. This study was designed to determine the heavy metals contamination in shrimp PL (post larvae) nurseries of Khulna region and associated human health risks. Water (raw sea water, treated and outlet water) and PL samples of five shrimp nurseries of Khulna districts were analyzed to measure the concentrations of six heavy metals (Zn, Cr, Mn, Cu, Pb and Ni) by using Atomic Absorption Spectrometer (Model No: AA-7000, Shimadzu). The metal concentrations were higher in almost all PL samples of five nurseries except Mn, which value was below detection level (BDL). Concentrations of Zn and Cu were significantly higher (P<0.05) in PL samples than inlet (raw sea water, treated water) and outlet water samples among five nurseries. The highest value for Cr was found in PL sample (2.95±3.64) ppm but the lowest was in outlet water (0.004±0.004) ppm. The highest value of Pb was found in PL samples (3.48±7.78) ppm and the lowest was in treated water sample (0.54±0.09). The Ni concentration was highest in PL samples (1.71±1.98) ppm while the lowest in both raw seawater (0.01±0.005) ppm and outlet water (0.01±0.004) ppm. In some PL samples, the concentrations of Cr, Cu, Pb and Ni were higher than maximum allowable concentration. The estimated daily intake (EDI) of heavy metals in shrimp PL were followed the order Zn>Cu>Pb>Cr>Ni>Mn. The target hazard quotients (THQ) of PL samples were followed the rank Pb>Cu>Zn>Ni>Cr>Mn. Target cancer risk (TR) of Pb of nursery-2 PL for rural people was 1.1305 × 10-4 while the urban and average TR was 1.4757× 10-4 and 1.2195× 10-4, respectively. The findings of the present study on heavy metal concentrations in PL nurseries indicate the necessities of quality water for prevention of accumulation heavy metals further in shrimp grown-up stages. Proper management strategies should be taken to avoid this risk. Bangladesh J. Zool. 48(1): 167-179, 2020